A dramatic effect of oxygen on protection of human cells against γ‐radiation by lycopene. Issue 8 (29th March 2016) - Boehm, Fritz; Edge, Ruth; Truscott, Terence George; Witt, Christian
Abstract : Reducing radiation damage is important and dietary antioxidants that can protect cells from such damage are of value. Dietary lycopene, a carotenoid found in tomatoes, protects human lymphoid cell membranes from damage by γ‐radiation. We report that such protective effects are remarkably reduced as the oxygen concentration increases – near zero at 100% oxygen from fivefold protection at 20% oxygen and, dramatically, from 50‐fold protection at 0% oxygen. Such huge differences imply that under higher oxygen concentrations lycopene could lead to improved cancer therapy using γ‐radiation. The cells are not efficiently protected from the superoxide radical by lycopene. Noncellular studies suggest molecular mechanisms for the oxygen effect. Abstract :